2015
DOI: 10.3767/003158515x688046
|View full text |Cite
|
Sign up to set email alerts
|

Towards a phylogenetic reappraisal of <I>Parmulariaceae</I> and <I>Asterinaceae</I> (<I>Dothideomycetes</I>)

Abstract: Members of the Asterinaceae and Parmulariaceae are obligate biotrophic fungi with a pantropical distribution that grow in direct association with living plant tissues and produce external ascomata and bitunicate asci. These fungi are poorly known, with limited information about their taxonomic position in the Dothideomycetes. Much of what is known is conjectural and based on observation of morphological characters. An assessment of the phylogenetic position of the Asterinaceae and Parmulariaceae is provided ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…The family Parmulariaceae comprises more than 30 genera with extremely varied characters and is polyphyletic (Guatimosim et al 2015). Genera such as Aldona, Aldonata, Dictyocyclus and Hemigrapha are not typical of the family when compared with the type (Inácio & Cannon 2008, Tian et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The family Parmulariaceae comprises more than 30 genera with extremely varied characters and is polyphyletic (Guatimosim et al 2015). Genera such as Aldona, Aldonata, Dictyocyclus and Hemigrapha are not typical of the family when compared with the type (Inácio & Cannon 2008, Tian et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Genera such as Aldona, Aldonata, Dictyocyclus and Hemigrapha are not typical of the family when compared with the type (Inácio & Cannon 2008, Tian et al 2015. There are few studies relating to the phylogeny of Parmulariaceae (Guatimosim et al 2015, Hyde et al 2016, Liu et al 2017, as genera of this family are unculturable, therefore it is hard to obtain their DNA sequence data. However, sequence data is available for Hemigrapha, Inocyclus and Parmularia with DNA extracted from fresh specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Inácio and Cannon (2008) designated specimens of I. psychotriae in K as lectotype, and in NY as isolectotype because the type material has not been seen. Guatimosim et al (2015) used sequence data of I. angularis in their phylogenetic tree and concluded that the phylogeny of Inocyclus in Parmulariaceae is unresolved because sequence data of type species is unavailable. The morphology of I. psychotriae ( Fig.…”
Section: Neoparodia Ekmaniimentioning
confidence: 99%
“…Fungi in the genus Asterina are cosmopolitan, but are most commonly found in the tropics, where ca. 90% of the species are described (Farr & Rossman, ; Guatimosim et al., ; Hosagoudar & Abraham, ).…”
Section: Introductionmentioning
confidence: 99%